Composition and distribution patterns of marine planktonic ostracods (Crustacea, Ostracoda) in the Adriatic Sea - a historical perspective - Brautović, Igor; Bojanić, Natalija; Vidjak, Olja; Grbec, Branka; Gangai, Barbara (2018)
This study provides the first comprehensive results on species composition, seasonal and horizontal distribution of the planktonic ostracod community in the open waters of the whole Adriatic Sea. Samples were collected during the “Andrija Mohorovičić” oceanographic expedition (1974-1976) in all four seasons at 35 stations located along eight latitudinal transects in the northern, central and southern part of the Adriatic Sea. Fifteen ostracod species and two subspecies belonging to the family Halocyprididae were identified. The dominant species were Archiconchoecia striata, Porroecia spinirostris and Proceroecia macroprocera. Additionally, Paraconchoecia oblonga was recorded for the first time in the Adriatic Sea. The highest abundance and diversity of planktonic ostracods were found in the deep South Adriatic. Conversely, ostracods were scarce in the shallow North Adriatic area. As the transitional zone between these two regions, the Central Adriatic was characterized by high ostracod diversity, but a short period of dominance in the zooplankton assemblage. The horizontal distribution of planktonic ostracods in the Adriatic Sea could be linked to periodical ingressions of Eastern Mediterranean water masses and gyre currents, especially in the Central and the South Adriatic.
Rad donosi prve sveobuhvatne rezultate o taksonomskom sastavu vrsta, sezonskoj i horizontalnoj raspodjeli zajednice planktonskih ljuskara u otvorenim vodama cijelog Jadranskog mora. Uzorci su prikupljeni tijekom oceanografske ekspedicije “Andrija Mohorovičić” (1974.-1976.) tijekom četiri godišnja doba na 35 postaja, raspoređenih u osam poprečnih transekata na sjevernom, srednjem i južnom dijelu Jadranskog mora. Taksonomski je određeno petnaest vrsta i dvije podvrste planktonskih ljuskara iz porodice Halocyprididae. Dominantne su vrste bile: Archiconchoecia striata, Porroecia spinirostris i Proceroecia macroprocera. Pored toga, vrsta Paraconchoecia oblonga je po prvi put zabilježena u Jadranskom moru. Najveća abundancija i bio-raznolikost ljuskara je zabilježena u dubokom južnom Jadranu, dok su bili rijetki u plitkom području sjevernog Jadrana. Kao prijelaznu zonu između ova dva područja, srednji Jadran karakterizira velika bio-raznolikost i kratkotrajna dominacija planktonskih ljuskara u zooplanktonskoj zajednici. Njihova horizontalna raspodjela u Jadranskom moru može se povezati s periodičnom ingresijom istočno-mediteranske vode i vrtložnim strujanjima, posebice u područjima srednjeg i južnog Jadrana.
Bibliografija: str. 86-89.
Summary ; Sažetak.
Keywords: Halocyprididae -- Planktonski ljuskari -- Sastav zajednice; Jadransko more